ANALISIS DAMPAK EKSPLOITASI MIGAS TERHADAP PERUBAHAN KEBIJAKAN TATA RUANG KABUPATEN BOJONEGORO - , Agus Setyawanto,Drs. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study empirical background that exploration and exploitation of oil and gas development conducted Exxon Mobile and Petro China in Bojonegoro become a fundamental factor in the problem structuring and changes in the region of space utilization. The amount of oil and gas content of an attraction potential drivers of change needs more space Bojonegoro Government committed to supporting economic development in Bojonegoro. Through a policy of "on going" by the Government Bojonegoro among others in the form of of granting permission to land area Exxon Mobile oil and gas exploitation and Petro China so the impact on zoning changes outside of the Spatial Planning and Regional (Spatial) Bojonegoro. The focus of analysis in this study, aimed at: a) a general description of mining oil and gas and chronological changes in zoning